Unleadership: The Remarkable power of unremarkable acts - Kars, Selen; Jarvis, Carol; Gaggiotti, Hugo (Berlin De Gruyter, 2024)
Leaderly acts and practices from unexpected places are often overlooked and yet have remarkable power. These spontaneous acts are in sharp contrast to those of formal leaders in governments and leading corporations. Global events like the Covid-19 pandemic and the climate crisis light up these differences. This book delves deeper, exploring these leaderly acts and practices more fully and beyond extraordinary events. The authors describe these as "unleadership", a term defined in this book as a set of acts and practices that are undertaken in a spirit of spontaneity and generosity for social good.
Keywords: Business; Economics